Pengaruh Pembiayaan Musyarakah Terhadap Pendapatan Bank BRI Syariah Indonesia Periode 2014-2020 - Noorulviah Beredhawati Atmaja; Siti Amallia Tadim; R. Deden Adhianto (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2021)
Consumer financing is one of the focuses of BRI Syariah financing distribution because it has a low risk. This is because consumer financing is based on mortgages and multi-purpose financing. This study aims to determine the effect of Musyarakah Financing on Income. This research was conducted at Bank BRI Syariah Indonesia for the period 2014 to 2020. This method uses a descriptive quantitative approach. The development of Islamic banking is also marked by an increase in the distribution of financing. Financing is very important because this financing factor is the key to the development of Islamic banks in the future. Ideally, Islamic bank financing is dominated by musharaka contracts which are run with a profit-sharing system. The data used in this study is secondary data derived from annual reports that can be accessed through the Financial Services Authority website in the form of an annual time series from 2014-2020. This study applies a simple linear regression data analysis method. Based on the results of research using the SPSS Version 20 statistical program, Musyarakah Financing (X) has a positive and significant effect on Income (Y).